2021
DOI: 10.21608/amj.2021.139848
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phototherapy on Zinc Status in Term Neonates With Indirect Hyperbilirubinemia

Abstract: Background: Jaundice is the most common clinical sign in neonatal medicine. Phototherapy is the most commonly used intervention to treat and prevent severe hyperbilirubinemia. Zinc has a vital role in maintenance of cell functions, protein synthesis, and immune-functions.Objective: To study the effect of phototherapy on zinc status in term neonates with indirect hyperbilirubinemia. Patients and methods:This was a prospective study carried out on 50 term neonates with indirect hyperbilirubinemia in neonatal int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…These properties could be valuable in heme catabolism and bilirubin production [108,109]. Its combination with phototherapy may be beneficial and safe for reducing the level of bilirubin and the duration of phototherapy in term and premature newborns with indirect jaundice [110][111][112][113]. A group of researchers tested and found that phototherapy has no effect on the level of zinc in the serum.…”
Section: Zinc Sulfatementioning
confidence: 99%
See 2 more Smart Citations
“…These properties could be valuable in heme catabolism and bilirubin production [108,109]. Its combination with phototherapy may be beneficial and safe for reducing the level of bilirubin and the duration of phototherapy in term and premature newborns with indirect jaundice [110][111][112][113]. A group of researchers tested and found that phototherapy has no effect on the level of zinc in the serum.…”
Section: Zinc Sulfatementioning
confidence: 99%
“…A group of researchers tested and found that phototherapy has no effect on the level of zinc in the serum. However, zinc supplements are encouraged in cases of neonatal jaundice, because they are usually zinc deficient [111]. On the other hand, another group of researchers claimed that it must be taken into account that there could be a risk of raising the level of zinc in the serum during phototherapy.…”
Section: Zinc Sulfatementioning
confidence: 99%
See 1 more Smart Citation